Crafting and executing strategy concepts and readings - Thompson, Arthur A. 1940-; Peteraf, Margaret Ann; Gamble, John; Strickland, A J III (McGraw-Hill/Irwin, 2012)
Includes a collection of 20 readings that amplify important topics in managing a company's strategy-making, strategy-executing process that provides students with a taste of the literature of strategic management before tackling cases or simulation projects